Malaysia a case study in unity - Abd Razak, Dzulkifli (2007)
THE prime minister, during his visit to BosniaHerzegovina recently, made an impact when he suggested that they copy Malaysia in nation building. He said Malaysia could serve as a tem plate for multiethnic, Muslimmajority BosniaHerzegovina. This came during his lecture at the University of Sarajevo where he was presented with the Golden Pin — the highest award by the university. The two countries share many similarities and thus can learn from one another.